Serum-free media supplements carry miRNAs that co-purify with extracellular vesicles. Issue 1 (1st December 2019) - Auber, Martin; Fröhlich, Dominik; Drechsel, Oliver; Karaulanov, Emil; Krämer-Albers, Eva-Maria
ABSTRACT: Recent studies on extracellular RNA raised awareness that extracellular vesicles (EVs) isolated from cultured cells may co-purify RNAs derived from media supplements such as fetal bovine serum (FBS) confounding EV-associated RNA. Defined culture media supplemented with a range of nutrient components provide an alternative to FBS addition and allow EV-collection under full medium conditions avoiding starvation and cell stress during the collection period. However, the potential contribution of serum-free media supplements to EV-RNA contamination has remained elusive and has never been assessed. Here, we report that RNA isolated from EVs harvested from cells under serum-replacement conditions includes miRNA contaminants carried into the sample by defined media components. Subjecting unconditioned, EV-free medium to differential centrifugation followed by reverse transcription quantitative PCR (RT-qPCR) on RNA isolated from the pellet resulted in detection of miRNAs that had been classified as EV-enriched by RNA-seq or RT-qPCR of an isolated EV-fraction. Ribonuclease (RNase-A) and detergent treatment removed most but not all of the contaminating miRNAs. Further analysis of the defined media constituents identified Catalase as a main source of miRNAs co-isolating together with EVs. Hence, miRNA contaminants can be carried into EV-samples even under serum-free harvesting conditions using culture media that are expected to be chemically defined. Formulation of miRNA-free media supplements may provide a solution to collect EVs clean from confounding miRNAs, which however still remains a challenging task. Differential analysis of EVs collected under full medium and supplement-deprived conditions appears to provide a strategy to discriminate confounding and EV-associated RNA. In conclusion, we recommend careful re-evaluation and validation of EV small RNA-seq and RT-qPCR datasets by determining potential medium background.